2012
DOI: 10.1098/rspb.2011.2276
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent symbioses and their potential roles in wildlife diseases

Abstract: It is well known in ecology, evolution and medicine that both the nature (commensal, parasitic and mutualistic) and outcome (symbiont fitness, survival) of symbiotic interactions are often contextdependent. Less is known about the importance of context-dependence in symbioses involved in wildlife disease. We review variable symbioses, and use the amphibian disease chytridiomycosis to demonstrate how understanding context-dependence can improve the understanding and management of wildlife diseases. In chytridio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 96 publications
(146 reference statements)
1
67
0
Order By: Relevance
“…Context dependency is common in both the establishment and maintenance of many facultative fungal symbioses and in the functional outcomes of such associations (43)(44)(45)(46)(47) and likely shapes the success of EHB-fungal encounters in nature. Our results reveal that nutrient conditions can be important for successful reassociations.…”
Section: Discussionmentioning
confidence: 99%
“…Context dependency is common in both the establishment and maintenance of many facultative fungal symbioses and in the functional outcomes of such associations (43)(44)(45)(46)(47) and likely shapes the success of EHB-fungal encounters in nature. Our results reveal that nutrient conditions can be important for successful reassociations.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient and persistent host and environmental colonization needs to be established: amphibian skin microbiomes are dynamic and can be unstable and unpredictable, and bacterial community composition changes over the animal's lifetime [32]. Bioaugmentation requires a deeper understanding of bacterial community assembly, stability and permeability, couched in the context of amphibian host community, the skin secretions produced by species members of the community and how these are in turn influenced by environmental heterogeneity [39,40]. Probiotics should also exert their beneficial effect across Bd genotypes.…”
Section: Trialled and Testedmentioning
confidence: 99%
“…The fitness impact of services provided by symbiotic interactions on the host is often strongly dependent on the ecological context (Daskin & Alford, 2012). Several studies have shown that the hosts' diet, especially food quality, can be an important influencing factor on interactions between the host and its gut microbiota.…”
Section: Introductionmentioning
confidence: 99%